Solvability for a system of Hadamard fractional multi-point boundary value problems - Xu, Jiafa; Liu, Lishan; Bai, Shikun; Wu, Yonghong (Nonlinear Analysis: Modelling and Control, 2021)
In this paper, we study a system of Hadamard fractional multi-point boundary value problems. We first obtain triple positive solutions when the nonlinearities satisfy some bounded conditions. Next, we also obtain a nontrivial solution when the nonlinearities can be asymptotically linear growth. Furthermore, we provide two examples to illustrate our main results.
Keywords: Hadamard fractional differential equations; multi-point boundary value problems; multiple solutions; asymptotically linear growth